Choosing party leaders: Anglophone democracies, British parties and the limits of comparative politics - Denham, Andrew (Palgrave Macmillan, 2017)
Since 1965, Britain’s major political parties have radically, and repeatedly, changed the ways in which they choose their leaders. Building on a recent comparative study of party leadership selection in the five principal Anglophone (‘Westminster’) parliamentary democracies (Cross and Blais, 2012a), this article first outlines a theoretical framework that purports to explain why the major parties in three of those countries, including Britain, have adopted such reform. It then examines why five major British parties have done so since 1965. It argues that, while Cross and Blais’ study makes a significant contribution to our knowledge and understanding of processes of party leadership selection reform in Anglophone parliamentary democracies, it has limited explanatory power when applied to changes enacted by the major parties in modern and contemporary Britain. Instead, the adoption of such reform in the British context is ultimately best understood and explained by examining both the internal politics and external circumstances of individual parties.